2020
DOI: 10.1111/rda.13833
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive season and male effect on quantitative and qualitative traits of individually collected Muscovy duck (Cairina moschata) semen

Abstract: Males of Muscovy duck (Cairina moschata) are mainly intended for the production of mule ducks-an intergeneric hybrids derived from crossing the Muscovy drake with females originated from wild mallard duck (Anas platyrhynchos). Those mule ducks are used both for 'foie gras' (duck fatty liver) production (Chen et al., 2016) and as duck broilers. Approximately 90% of ducks used for fatty liver production in France are mule ducks (Bonnefont et al., 2019), and only 5% are pure lines of Muscovy duck (Marie-Etancelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The cited authors showed that, similarly to our experiment, bulb-head sperm constituted the highest percentage among the abnormal forms. In addition, in our research on ducks ( Łukaszewicz et al, 2020a , c ), capercaillie ( Kowalczyk et al, 2012 ), pigeons ( Klimowicz et al, 2005 ), and chicken broiler breeders ( Łukaszewicz et al, 2020b ), bulb-head sperm were observed the most frequently. Chełmońska et al (1984) found less live sperm in total (86.2–89.0%) in Kubańska goose semen in relation to both, the northern and southern regional group, but significantly more properly formed sperm (55.7%), especially compared to Rypińska, Kielecka, and Lubelska breeds.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The cited authors showed that, similarly to our experiment, bulb-head sperm constituted the highest percentage among the abnormal forms. In addition, in our research on ducks ( Łukaszewicz et al, 2020a , c ), capercaillie ( Kowalczyk et al, 2012 ), pigeons ( Klimowicz et al, 2005 ), and chicken broiler breeders ( Łukaszewicz et al, 2020b ), bulb-head sperm were observed the most frequently. Chełmońska et al (1984) found less live sperm in total (86.2–89.0%) in Kubańska goose semen in relation to both, the northern and southern regional group, but significantly more properly formed sperm (55.7%), especially compared to Rypińska, Kielecka, and Lubelska breeds.…”
Section: Discussionmentioning
confidence: 67%
“…For a practical reason, as well as economic aspects and availability of specific test methods, it is important that the evaluation method is reliable, but also simple, cheap, and possible to be made in a farm condition. Our to date research shows that one of the most reliable methods of semen quality assessment is not the determination of total amount of sperm in the ejaculate, but the number of live properly formed sperm, because only such sperm have the highest potency to fertilize an egg ( Bakst et al, 1994 ; Liu et al, 2008 ; Zawadzka et al, 2015 ; Łukaszewicz et al, 2020a , b , c ).…”
Section: Introductionmentioning
confidence: 99%
“…Sperm cell concentration in Muscovy semen is high i.e. , it is viscous [ 5 , 6 ]. In practice, diluted and short-term stored semen is increasingly used in order to increase the number of inseminated birds.…”
Section: Introductionmentioning
confidence: 99%
“…A significantly lower percentage of positively reactions of Zi (Anser cygnoides L.) and Rhin (Anser anser L.) ganders (30% and 46% respectively) were described by Liu et al (2014), and Hungarian ganders (30%) - Almasi et al (2002) and Varga et al (2003). A varied level of reaction has also been observed in males of other bird species (Gerzilov, 2004;Liu et al, 2014;Łukaszewicz et al, 2020).…”
Section: Discussionmentioning
confidence: 74%